WULF'S BANE - Delaney, Joseph, 1945- (London : Puffin, 2021)
Wulf has left behind his life in the monastery and is now the Apprentice to Spook Johnson, assisting him in protecting the County from denizens of the dark - which mainly involves Wulf acting as bait. But Wulf is captured by Hrothgar, a giant with abilities to conjure subservient creatures - or tulpas - from his imagination. And he strongly suspects that Wulf has these abilities too. Wulf begrudgingly begins training with his new master, but meanwhile, something dangerous is afoot in the County. Wulf's old friends, Tom and Alice, have been imprisoned by an all-powerful witch and her brain sucking minions. And together with Tilda, Tom and Alice's daughter, he needs to rescue them from Circe's enchanted lair before it's too late
"A spook's apprentice adventure"--Cover.
Keywords: Ward, Thomas -- (Fictitious character) -- Fiction; Monks -- Fiction; Apprentices -- Fiction; Magic -- Fiction